Identification of Novel Environmental Substances Relevant to Pediatric Graves’ Disease - Xia, Qin; Liu, Jingjing; Xu, Xu; Gu, Wei; Gu, Kefeng; Chen, Xiuli; Xie, Rongrong; Zhang, Dandan; Wu, Haiying; Sun, Hui; Wang, Fengyun; Chen, Linqi; et al. (Frontiers in Endocrinology, 2021)
Graves’ disease (GD) is the most common cause of hyperthyroidism, yet a relatively rare disease in the pediatric population. GD is a complex disorder influenced by both genetic and environmental factors. In this study, we aimed to find new environmental factors influencing the pathogenesis of GD. We investigated serum substances in 30 newly diagnosed GD children and 30 age- and gender-matched healthy controls. We measured total iodine by inductively coupled plasma-mass spectrometry (ICP-MS), analyzed perfluorinated compounds via ultra-high-performance liquid chromatography coupled with multiple reaction monitoring mass spectrometry (UHPLC-MRM-MS), and explored other environmental substances using ultra-high-performance liquid chromatography–quadrupole time-of-flight mass spectrometry (UHPLC-QTOF/MS) analysis. Twenty-nine single-nucleotide polymorphisms (SNPs) in 8 genes related to GD were analyzed by SNaPshot. The serum total iodine was significantly higher in GD group, but its association with GD onset was weak, only with Exp(B) value near 1. The perfluorinated compounds levels were not different between the two groups. More importantly, we found 16 environmental substances significantly different between GD and control groups, among which ponasterone A is a risk factor (p=0.007 and Exp(B)=14.14), while confertifoline is a protective factor against GD onset (p=0.002 and Exp(B)=0.001). We also identified 10 substances correlated significantly with thyroid indices in GD patients, among which 7 associated with levels of the thyroid autoantibody TPOAb. No known SNPs were found predisposing GD. In this study, we explored a broad variety of environmental substances and identified novel factors that are potentially involved in the pediatric GD pathogenesis.